PEHS: arquitetura de um sistema eletrônico de saúde pervasivo orientado às atividades do usuário clínico - Vicentini, Caroline Fighera (2010)
In despite of the great advantages of adopting computer systems for storing patient's information in hospitals and clinics, such systems are adopted with restrictions in these institutions. Some studies indicate that the rejection of such systems by the clinicians is greats due to computing not consider the particularities of the activities performed by the user in the clinical field. Considering this background, the project ClinicSpace aims to build a prototype tool to help health professionals in performing of their activities, using concepts and technologies of ubiquitous computing, which suggests that the computation must be fully integrated into the environment, disappearing from the user's consciousness and assisting him in their daily activities. This paper proposes an architecture called pEHS - Pervasive Electronic Healthcare System - a electronic health system inserted in the ClinicSpace's proposal, where the computing is oriented to clinical activities and the applications do interact with the ubiquitous environment through context information. The contribution of this paper is the proposal of a new software architecture in which pEHS modular applications follows the medical activities, making the system to adapt to the clinician's activities. In the architecture there are two points in evidence: the possibility of access to any information from the patient's health history and the adaptation of pEHS applications to the context information at runtime. The prototyped architecture will be used in the ClinicSpace project to build the applications needed for the clinicians helping them to carry out their activities.